Propagation Characteristics of Rectangular Hermite-Gaussian Array Beams Through Oceanic and Atmospheric Turbulence - Hao Du; Guixuan Ding; Xing Du; Zhenyang Xiong; Sheng Wang; Qiang Liu; Hui Feng; Simeng Wang (IEEE Photonics Journal, 2023)
This study investigates the propagation characteristics of rectangular Hermite-Gaussian array beams (RHGABs) through the oceanic and atmospheric turbulence considering ocean waves. Firstly, a theoretical model for the RHGABs in seawater-to-air propagation path is proposed. Secondly, we derive the expressions of the mean squared beam width and angular spread of RHGABs by using the extended Huygens-Fresnel principle and Rytov approximation. Finally, the effects of turbulent mediums on the RHGABs spreading are studied by analyzing the Rayleigh range. Our findings suggest that the Rayleigh range increases with the beam order of RHGABs. And the mean squared beam width of RHGABs in oceanic turbulence increases significantly higher than that in atmospheric turbulence. The results of this research can be applied to underwater optical communication systems.